The Impact of Dust and Salt Aerosols of the Aral Sea on the Tissues of Rat Testes in the Experiment - Suleimen, A.; Yesimova, R.; Rakhimova, B.; Suleimen, G.; Yerubay, A.; Britko, V.; Aitkulov, A.; Kultanov, B. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The Aral Sea crisis is recognized as one of the global environmental problems of our time. The extreme environmental situation in the region is caused by massive chemical pollution of the territory for several decades by high doses of pesticides, herbicides, dumping of industrial waste into the rivers that feed the Aral Sea. As a result of the Aral Sea desiccation, aridization of the territory, climate change, and salinization of soil and water occurred. This led to increased mineralization of precipitation, climate change, the spread and deposition of dust on an area of about 25 million hectares. One of the factors in reducing fertile activity in humans is a decrease in spermatogenesis activity. Based on identified trends, WHO is forced to review the main indicators of spermograms in the direction of their reduction. AIM: To study the effect of dust and salt aerosols of the Aral Sea on reproductive function, rat testes were studied after 7 and 24 days of inhalation administration. MATERIAL AND METHODS: Some morphometric parameters of the testes were evaluated: The diameter of the convoluted seminiferous tubules and the thickness of the germinal epithelium. The obtained comparative morphological and histological characteristics of the testes of the control and experimental groups indicate the negative effect of the components of dust and salt aerosols of the Aral Sea on the reproductive function of male rats. RESULTS: The thickness of the epithelial spermatogenic layer in the second group of rats is on average 64.52 μm, which is significantly less compared to the control group (81.3 μm). The thickness of the epithelial spermatogenous layer in the third group is on average within 73.36 μm, which is significantly less than in the control group (81.3 μm), but more than in the group exposed to dust and salt aerosols for 7 days (64, 52 μm). CONCLUSION: The study revealed that the impact of dust and salt aerosols of the Aral Sea leads to a change in the morphological and histological characteristics of the testes of animals. In experimental groups, a decrease in the diameter of the convoluted seminiferous tubule and a decrease in the thickness of the epithelial spermatogenic layer were observed. This indicates the negative effect of the components of dust and salt aerosols of the Aral Sea on the reproductive function of male rats exposed to dust for 7 and 24 days.
Keywords: Dust and salt aerosols; Aral Sea; rat testes